Кон Fabrice Midal, Quel bouddhisme pour l’Occident? Për Fabrice Midal, Quel bouddhisme pour l’Occident? - Sekulovski, Jordančo; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Jordančo Sekulovski | Јорданчо Секуловски Title (Macedonian): Кон Fabrice Midal, Quel bouddhisme pour l’Occident? Title (Albanian): Për Fabrice Midal, Quel bouddhisme pour l’Occident? Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 181-183 Page Count: 3 Citation (Macedonian): Јорданчо Секуловски, „Кон Fabrice Midal, Quel bouddhisme pour l’Occident?“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 181-183. Citation (Albanian): Jordančo Sekulovski, „Për Fabrice Midal, Quel bouddhisme pour l’Occident?“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 181-183.